Relationship of Physical Activity and Eating Practices with BMI; Barriers to Physical Activity and Optimum Eating Practices among Medical Students of Islamabad - Muddasar Pervaiz, Muhammad Hamza, Mahvesh Mahmud, Ayesha Javaid, Iram Yasir, Muhammad Ammar (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To identify levels of the physical activity and patterns of eating habits among medical students of Islamabad and to determine the association of BMI with physical activity and eating habits among medical students of Islamabad. Study Design and Setting: A cross-sectional survey was done in a private and public medical college of Islamabad. Methodology: A total of 463 MBBS students of 1st year to 5th year were included and data was collected by non-probability convenience sampling. Before initiating study enrolment an ethical approval for study was gained from the institutional ethical board. After signing the consent form, the questionnaire was filled formally. Data was analyzed by SPSS 22.0. P value < 0.05 was considered as statistically significant Results: 236 of our population were normal and 117 of our population were overweight, whereas 59 were underweight and 51 were obese. Lack of time for physical activity in time table was the most common occurring barriers of physical activity. The most common occurring barrier to optimum eating practices were lack of money, tasty fast food and don’t like home cooked food. Results showed statistically significant relationship between the hours of exercise per week and the BMI status. The Chi-Square value (P-Value) for physical activity and eating habits in association with BMI were 0.228 and 0.570 were insignificant. Conclusions: Results concluded that bad eating habits and lack of physical activity affects the BMI. Individuals in obese group had increased BMI, lack of physical activity and bad eating habits.